SI JUKI VS. EMPTY WALLET COMIC ANALYSIS. CRITICAL DISCOURSE REVIEW TEUN A VAN DIJK - Rahayu, Enny (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
This study aims to describe the Critical Discourse Review of Teun A Van Dijk in the comic Si Juki vs Dompet Blank”. This research is a qualitative descriptive study. The method used in this research is the method of data collection and documentation. The data sources in this research are macro structure, super structure, and microstructure which are analyzed directly from the comic Si Juki Vs Dompet Blank. The result of this research is the comic Si Juki Vs Dompet Kososng. From the research results, macro structure, theme; to increase public knowledge about mercury investment. Topics; can start moving to learn to manage finances. Super structure, semantics; In the comic Si Juki Vs Dompet Blank there are two different texts, namely descriptive text, and exposition text. Macro structure; semantics: readers can begin to be moved to learn to manage their finances, stylistics; the choice of words used in the comic Si Juki Vs Dompet Blank is easy to understand because the words used are simple and commonly used in public places, the lexicon; office, boarding, and savings.